Python online exam system - Doan, Duy Duc (2018)
Technology is adopted widely in different modern education activities. This also applies to the evaluating process with quiz and test paper. After assessment on several online testing systems, there is a need for a user-friendly and fully functional system that supports various types of questions in quizzes especially coding questions for computer science courses. This report summarizes the development process of QuizSys - a quiz issuing websites that allow different levels of quiz management and evaluation in the final year project SCE17-0217 under the supervision of Dr. Li Fang. The working process comprises of full-stack development with both backend and frontend development. The backend is based on Django REST framework to create a JSON API Server while the frontend aims at serving a dynamic website with user friendly interface. The project has completely set up the working structure of the system and open for maintenance and extension.